Perfil epidemiológico, clínico e laboratorial de pacientes portadores de hipertireoidismo atendidos no hospital universitário João de Barros Barreto - Período de julho de 1993 a janeiro de 2005 - GALÚCIO, Aline Libonati (2022)
The hyperthyroidism is one of the main disease of thyroid, with on its incidence about 2% of the population of women. It is defined by the increase of the thyroid’s function represented by the rise of T4 and T3, resulting in thyrotoxic characterized by the accelerate metabolism of the organism. The main objective of this study was to know the profile epidemiologist, physician and laboratorial of patients with hyperthyroidism taken care of in the clinic of endocrinology of the HUJBB. It was a serial study of cases with a sample of 210 patients, and by means of a research protocol, interview with the patients was made and searches of data of the handbook. Of the 210 studied patients, the majority (29%) was in the age band of 40 the 49 years and 180 (85,7%) had been of the feminine sex. The hyperthyroidism cause most frequent was the Graves’ disease, occurring in 164 patients (78.1%). The main symptoms and signals had been palpitation (75.2%), nervousness (61.4%), fatigue (55.2%), goiter (89.5%), weight loss (74.3%) and tremors (73.3%). Systemic arterial hypertension was main associated disease (8.6%) and arrhythmias were the main complication (5.7%). The average of the dosage of TSH was 0,0690,172 UuI/ml and of free T4 was 5,082,82 ng/dl. The main electrocardiographic alteration was sinusal palpitations, followed for atrial fibrillation. Of the 22 patients who had made ecocardiogram, mitral valve with low ebb was main finding 9 (40.9%). The use of anthyroid drugs was the first therapeutical choice, used in 205 (97.6%) patient ones, being that only 48 patients (23.4%) had had remission of hyperthyroidism. The partial tyroidectomy was carried through in only 5 patients, having been the cure observed in only 20% of the cases. The radioactive iodine was used in 93 patients with average of the dosage of 13,24,3 mCi. The accompaniment average during the study was 8,59,75 months, in this period 12 (19%) had become euthyroid, eighteen (28%) had evolved for hypothyroidism and nine (14.1%) needed to make the second dose of iodine. One concludes that the profile of the patients with hyperthyroidism taken care of in the HUJBB was similar to the observed one in world-wide literature.